2017
DOI: 10.1007/s12094-017-1630-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of neutrophil/lymphocyte ratio and platelet/lymphocyte ratio with ER and PR in breast cancer patients and their changes after neoadjuvant chemotherapy

Abstract: The patients with low pretreatment NLR (<2.05) or PLR (<159.01) had higher ER expression. Changes in ER and PR expression status or level occured following NAC. Elevated PLR was found aft-NAC. Pretreatment NLR and PLR may be important predictive indicators for NAC response in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
2
28
3
Order By: Relevance
“…Again, this study confirmed the association of a high NLR with worse survival, but importantly, also with recurrencefree survival after neoadjuvant chemotherapy [21]. Yet another study evaluating the response to neoadjuvant chemotherapy found that patients with low pretreatment NLR had better responses, although their cut-off for what was considered a 'low' NLR varied from the aforementioned report [22]. This highlights one of the issues associated with the classification of NLR, in that there is not a strictly defined cut-off value for its analysis.…”
Section: Nlrpredictive Of Metastasis?supporting
confidence: 68%
“…Again, this study confirmed the association of a high NLR with worse survival, but importantly, also with recurrencefree survival after neoadjuvant chemotherapy [21]. Yet another study evaluating the response to neoadjuvant chemotherapy found that patients with low pretreatment NLR had better responses, although their cut-off for what was considered a 'low' NLR varied from the aforementioned report [22]. This highlights one of the issues associated with the classification of NLR, in that there is not a strictly defined cut-off value for its analysis.…”
Section: Nlrpredictive Of Metastasis?supporting
confidence: 68%
“…Its prognostic value, however, should be regarded with caution and detailed clinical evaluation is needed before the ultimate prognostic significance of NLR in BC can be determined. Additional studies are required to prospectively evaluate the clinical value of pre-treatment NLR in BC, or its predictive significance for treatment response (31,32,39) and/or adverse events (40). Nevertheless, we believe that its determination might provide important information regarding risk stratification, especially in stage I patients in whom the presence of high NLR might raise the question as to whether they should be more aggressively managed.…”
Section: Resultsmentioning
confidence: 99%
“…53 In Xu et al research, their study showed that the patients with lower pretreatment NLR (<2.05) or PLR (<159.01) will have higher ERpositive expression, the patients with low NLR or low PLR would have a higher rate of complete remission (CR) and partial remission (PR) ( Figure 4A-D). 7…”
Section: Nlr and Plrmentioning
confidence: 99%
“…Recent epidemiological and clinical studies have found that inflammatory responses are associated with breast tumors. 6,7 Inflammation constitutes part of the tumor microenvironment, and changes in inflammatory cells affect tumor progression, including breast cancer cell proliferation, invasion, decreased immunity, metastasis, and so on. 8,9 Tumor inflammatory response may be a potential target for treating tumors.…”
Section: Introductionmentioning
confidence: 99%